Possible approach for the simultaneous measurement of temperature and strain via first- and second-order diffraction from bragg grating sensors - Kalli, Kyriacos; Jackson, David A.; Webb, David J. (My University, 1995)
A new method of discriminating between temperature and strain effects in fiber sensing, using a single, conventionally written in-fiber Bragg grating, is presented. The technique is based on a dual wavelength scheme and uses wavelength information from the first and second order diffraction from a single grating element when illuminated with light coinciding with the primary and secondary reflecting wavelengths. It is often assumed that during the grating growth the fiber core responds linearly to the incident UV radiation, thus resulting in a sinusoidal refractive index profile and only one discrete wavelength being reflected. In practice the recording process is nonlinear with continued exposure of the grating resulting in saturation of the index perturbation, this results in higher order grating reflections at roughly integer multiples of the primary reflected optical frequency, i.e. 1/integer multiples of the incident wavelength. The determination of the wavelength dependent strain and temperature coefficients at the primary and secondary reflections can be used to give independent temperature and strain measurements.
Keywords: Bragg gratings; Diffraction gratings; Refractive index; Temperature measurements